SOCIO-AFFECTIVE STRATEGY USED BY EFL STUDENTS DURING THE COVID-19 PANDEMIC AT SMP MUHAMMADIYAH PALANGKA RAYA - Rahmadi Nirwanto; Siti Suryani; Aris Sugianto (IKIP Siliwangi, 2022)
Socio-affective strategies relates to socially The Sample was random sampling technique. This research was conducted in order to determine the learning outcomes obtained quantitatively by conducting a survey of 45 students at SMP Muhammadiyah Palangka Raya. The information was gathered through the use of a questionnaire. The survey found that the majority of students in the speaking class used their own tactics. There were six students studying at the time. This showed that each learning strategy affected the progress of students in the English speaking class. It meant that the students' strategies affected their progress in obtaining learning outcomes in their learning progress while speaking class. In conclusion the most students in speaking class have their own learning strategies. Not only 6 strategies that can affect student learning abilities, but also the others can affect too, such as psychological factors, the role of teachers, assignments, environmental and social factors. Keywords: Socio-Affective Strategy, EFL Learning, Covid-19 Learning